The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1107/s2053229618016972
|View full text |Cite
|
Sign up to set email alerts
|

A series of two-dimensional lanthanide coordination polymers: synthesis, structures, magnetism and selective luminescence detection for heavy metal ions and toxic solvents

Abstract: A series of two‐dimensional (2D) coordination polymers (CPs), namely poly[[bis(μ‐acetato)diaqua(μ6‐biphenyl‐3,3′,5,5′‐tetracarboxylato)bis(N,N‐dimethylacetamide)digadolinium(III)] N,N‐dimethylacetamide monosolvate], {[Gd2(C16H6O8)(C2H3O2)2(C4H9NO)2(H2O)2]·C4H9NO}n (CP1), poly[[bis(μ‐acetato)diaqua(μ6‐biphenyl‐3,3′,5,5′‐tetracarboxylato)bis(N,N‐dimethylacetamide)didysprosium(III)] N,N‐dimethylacetamide monosolvate], {[Dy2(C16H6O8)(C2H3O2)2(C4H9NO)2(H2O)2]·C4H9NO}n (CP2), poly[bis(μ‐acetato)diaqua(μ6‐biphenyl‐3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…One type is M-L-M and the second one is a Mn 2 L 2 ring to make this an unusual 4-connected net (Figure ) with 2-fold interpenetration . Few other examples on rectangular grids based 2D MOFs have been reported in the literature. …”
Section: Design Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…One type is M-L-M and the second one is a Mn 2 L 2 ring to make this an unusual 4-connected net (Figure ) with 2-fold interpenetration . Few other examples on rectangular grids based 2D MOFs have been reported in the literature. …”
Section: Design Strategiesmentioning
confidence: 99%
“…For electrically conductive Cu­(II) 2D MOFs, Dincǎ et al . demonstrated chemiresistive sensing of VOCs through linear discriminant analysis and ambient CO 2 with RH sensitivity (400–2500 ppm). , A few more reports on solvents, VOCs, and gas sensing appeared in the literature. ,,,,, …”
Section: Properties and Applicationsmentioning
confidence: 99%
“…Subsequently, an isostructural RE-CP (1-Y) was obtained through identical procedure (Scheme 1). 39,40 With careful adjustment of the relative ratio of Y 3+ /Eu 3+ and Y 3+ /Tb 3+ , two series of isomorphous RE-CPs, namely Eu x Y 1Àx and Tb x Y 1Àx , were successfully obtained through isomorphous substitution technique (Scheme 2). The powder X-ray diffraction (PXRD) proved the isostructural structures of the doped complexes and the pure RE-MOF ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…As a new type of multifunctional nanoporous material, metal–organic frameworks (MOFs) constitute a type of crystalline framework material formed by chemical self‐assembly of inorganic metal ions or clusters and organic ligands. [ 17–20 ] Based on the chemical properties of high specific surface area, high porosity, and controlled pore size, the proton conductivities of MOF materials have caught the attention of researchers both at home and abroad. [ 21–26 ] It is reported that MOF materials can have low‐temperature (<373 K) and high‐temperature (>373 K) proton conductivity depending on structures.…”
Section: Introductionmentioning
confidence: 99%